Pemberdayaan Petani dalam Meningkatkan Ketahanan Pangan (Studi di Desa Betet Kecamatan Ngronggot Kabupaten Nganjuk) - Laily, Sean Fitria Rohmawati (Jurnal Administrasi Publik, 2014)
Abstract: The Peasant Empowerment to Increasing of Food Endurance (Study in Betet Village Ngronggot District Nganjuk Regency). In context of human life, food source is the most important needs. But nowdays, scarcity often appear in many place in Indonesia. It is appropriate with decentralization mandate, local government should make a program for peasant empowerment to achieve food endurance, it’s also occur for Betet Village, Ngronggot District, Nganjuk Regency. This research study used descriptive qualitative approach was done through observation, interviews and documentation. The model used data analysis is a data analysis model Miles and Huberman. The result of this study is about the empowernment of peasants conducted to increasing food endurance in the Betet Village considered better in improving food endurance, where the resulting production increases due to the knowledge and skills of the peasants in growing crops also increased. The major factors supporting success in improving food endurance in Betet Village is the implementation of empowernment programs provided by the local government, local government support and the assistance and seed subsidies to support productivity of agricultural production. The inhibiting come from the low quality of human resources, as well as the limitation of agricultural equipment. It’s needful of synergy between peasants, society and government working purposefully together to support of peasant empowerment program to increasing food endurance. For that, we need the synergy among peasants, society and government to joint supportly the empowernment of peasants in increasing food endurance. Keyword: Empowernment, Peasant, Food Endurance. Abstrak: Pemberdayaan Petani dalam Meningkatkan Ketahanan Pangan (Studi di Desa Betet Kecamatan Ngronggot Kabupaten Nganjuk). Dalam kontek kehidupan manusia sangat dibutuhkan sumber pangan. Namun, dewasa ini kelangkaan kerap muncul di berbagai tempat di Indonesia. Untuk itu Pemerintah Daerah sesuai dengan amanat desentralisasi harus mampu membuat program untuk pemberdayaan petani guna mewujudkan ketahanan pangan,tak terkecuali Desa Betet Kecamatan Ngronggot Kabupaten Nganjuk. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekaktan deskriptif yang dilakukan melalui observasi, wawancara dan dokumentasi. Model analisis data yang digunakan adalah model analisis data Miles dan Huberman. Hasil penelitian ini yaitu tentang pemberdayaan petani yang dilakukan di Desa Betet dapat dikatakan sudah lebih baik dalam mewujudkan ketahanan pangan. Dimana produksi yang dihasilkan menjadi lebih baik dan meningkat,ini dikarenakan pengetahauan dan keterampilan petani dalam bercocok tanam juga meningkat. Faktor pendukung utama keberhasilan peningkatan ketahanan pangan di Desa Betet adalah berjalannya program dengan adanya dukungan dari Pemerintah Daerah serta adanya bantuan subsidi dan benih. Hambatannya datang dari masalah rendahnya kualitas sumber daya manusia serta keterbatasan alat pertanian. Hal ini diperlukan adanya sinergi diantara petani, masyarakat serta pemerintah untuk secara bersama-sama mendukung program pemberdayaan petani untuk meningkatkan ketahanan pangan. Kata kunci: Pemberdayaan, Petani dan Ketahanan Pangan.